AI-Driven Mobile Learning in Enhancing Learners’ Speaking Confidence in EFL Context - Rangga Mauluddino Putra; Muhlisin Rasuki; Indri Astutik (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This article explores the effectiveness of Duolingo as an Artificial Intellegence (AI) based mobile-assisted language learning in improving English speaking confidence among English as a foreign language (EFL) learner. Using a library research method, this study synthesizes findings from peer-reviewed articles published between 2020 and 2025. The review identifies mechanism through Duolingo in enhances confidence, including gamification-based motivation, reduced-pressure speaking practice, and AI-driven pronunciation feedback. The analysis further highlights pedagogical strengths, limitations, and contextual factors that influence learner perceptions. The study concludes that Duolingo has consistent potential to enhance learners’ speaking confidence, particularly when used as a supplementary tool in technology-enhanced learning environments.